2009
DOI: 10.1016/j.jmpt.2009.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Effect of Ultrasound and Ischemic Compression Techniques for the Treatment of Trapezius Latent Myofascial Trigger Points in Healthy Subjects: A Randomized Controlled Study

Abstract: In this group of participants, both treatments were shown to have an immediate effect on latent MTrPs. The results show a relation among AROM of cervical rachis, BEA of the trapezius muscle, and MTrP sensitivity of the trapezius muscle gaining short-term positive effects with use of IC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
96
1
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(110 citation statements)
references
References 27 publications
5
96
1
3
Order By: Relevance
“…Embora não se conheçam trabalhos que estudaram conjuntamente a eletromiografia dos músculos cervicais e a medida da amplitude do movimento cervical em indivíduos com DTM, uma relação entre estes instrumentos foi parcialmente estabelecida por Aguilera et al 22 . Estes pesquisadores utilizaram diferentes tratamentos miofasciais para pontos gatilhos latentes do músculo trapézio, obtendo redução na atividade elétrica com consequente aumento da flexão lateral cervical, mas sugerem estudos que expliquem o mecanismo de estabelecimento desta relação.…”
Section: Discussionunclassified
“…Embora não se conheçam trabalhos que estudaram conjuntamente a eletromiografia dos músculos cervicais e a medida da amplitude do movimento cervical em indivíduos com DTM, uma relação entre estes instrumentos foi parcialmente estabelecida por Aguilera et al 22 . Estes pesquisadores utilizaram diferentes tratamentos miofasciais para pontos gatilhos latentes do músculo trapézio, obtendo redução na atividade elétrica com consequente aumento da flexão lateral cervical, mas sugerem estudos que expliquem o mecanismo de estabelecimento desta relação.…”
Section: Discussionunclassified
“…The results of a study by Okhovatian et al on LMTP located in the upper trapezius showed that ischemic compression significantly increased the pain threshold and statistically significantly decreased pain intensity [26]. In addition, the results of a study by Aguilera et al showed that immediately after the application of ischemic compression, pain intensity according to the VAS was statistically significantly lower compared to that registered prior to the application of ischemic compression [31]. The results of a study by Fryer et al showed that in subjects with LMTP in the upper trapezius, an ischemic compression procedure lasting 60 seconds statistically significantly decreased the pain threshold [34].…”
Section: Discussionmentioning
confidence: 94%
“…In order to ensure the effectiveness of ischemic compression, pain of 7-8 points was maintained throughout the procedure -i.e., if the subject reported a decrease in pain, the pressure was increased until the pain reached 7-8 points again. Aguilera et al in their study used the same duration of ischemic compression [31]. AL-Shawabka et al [32] Chao et al [33] and Okhovatian et al [26] in their studies applied ischemic compression for 60 second or until pain disappeared, depending on which occurred first.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion criteria for having active TP in UT muscle were as follow [26,27] The selected TP of the UT muscle was located in the middle of the UT muscle.…”
Section: Study Participantsmentioning
confidence: 99%